Gene expression analysis of B-lymphoma cells resistant and sensitive to bortezomib. - Shringarpure, R; Catley, L; Bhole, D; Burger, R; Podar, K; Tai, Y; Kessler, B; Galardy, P; Ploegh, H; Tassone, P; Hideshima, T; Mitsiades, C; et al. (2006)
The proteasome inhibitor bortezomib has shown impressive clinical activity alone and in combination with conventional and other novel agents for the treatment of multiple myeloma (MM). Although bortezomib is known to be a selective proteasome inhibitor, the downstream mechanisms of cytotoxicity and drug resistance are poorly understood. However, resistance to bortezomib as a single agent develops in the majority of patients, and activity in other malignancies has been less impressive. To elucidate mechanisms of bortezomib resistance, we compared differential gene expression profiles of bortezomib-resistant SUDHL-4 and bortezomib-sensitive SUDHL-6 diffuse large B-cell lymphoma lines in response to bortezomib. At concentrations that effectively inhibited proteasome activity, bortezomib induced apoptosis in SUDHL-6 cells, but not in SUDHL-4 cells. We showed that overexpression of activating transcription factor 3 (ATF3), ATF4, ATF5, c-Jun, JunD and caspase-3 is associated with sensitivity to bortezomib-induced apoptosis, whereas overexpression of heat shock protein (HSP)27, HSP70, HSP90 and T-cell factor 4 is associated with bortezomib resistance.